2018
DOI: 10.1038/s41467-018-04412-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-activated surface dynamics in gold catalysts under reaction environments

Abstract: Nanoporous gold (NPG) with sponge-like structures has been studied by atomic-scale and microsecond-resolution environmental transmission electron microscopy (ETEM) combined with ab initio energy calculations. Peculiar surface dynamics were found in the reaction environment for the oxidation of CO at room temperature, involving residual silver in the NPG leaves as well as gold and oxygen atoms, especially on {110} facets. The NPG is thus classified as a novel self-activating catalyst. The essential structure un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 28 publications
3
29
0
Order By: Relevance
“…Finally, the films floated on the surface of ultrapure water, and they were NPG pieces. This synthesis is the same as reported [34][35][36][37][38] . For conventional and in situ TEM characterizations, conventional TEM grids and sample chips from the DENS solutions company at The Netherlands were used, respectively, to collect NPG pieces from the water surface.…”
Section: Methodssupporting
confidence: 54%
See 2 more Smart Citations
“…Finally, the films floated on the surface of ultrapure water, and they were NPG pieces. This synthesis is the same as reported [34][35][36][37][38] . For conventional and in situ TEM characterizations, conventional TEM grids and sample chips from the DENS solutions company at The Netherlands were used, respectively, to collect NPG pieces from the water surface.…”
Section: Methodssupporting
confidence: 54%
“…The NPG samples were prepared by dealloying, and they possess bicontinuous pore channels and ligaments [32][33][34][35][36][37][38] . For instance, the as-prepared sample in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been demonstrated that these may enhance also the interaction between gold and the surface of the oxide [2]. Consequently, the reduction of the catalyst could counteract the sintering produced by the increase in temperature, taking also into account the possible dynamic re-dispersion of deposited gold nanoparticles in different supports depending on the atmosphere reported in literature [2,40,41]. However, this has to be confirmed and deeply analyzed through further experiments revealing more insights about the effects of the activation process in the studied catalysts.…”
Section: Catalytic Activity Measurementsmentioning
confidence: 97%
“…Electronically induced atomic and molecular dynamics must be elucidated in real time, real space, and real environments toward further advancing any scientific, engineering, and industrial fields. It has recently been reported that the atomic dynamics can be captured on the surface of a solid catalyst as a result of electronic reactions in a reaction environment . The catalytic reaction is considered to be triggered by the random collision of reactive gas molecules with the catalyst surface.…”
Section: Figurementioning
confidence: 99%